Optimization of School Health Efforts at Pesantren Kampung Tauhid Sriwijaya, Ogan Ilir Regency, South Sumatra Province - Wardiansyah; Indri Seta Septadina (Fakultas Kedokteran Universitas Sriwijaya, 2020)
School health business, abbreviated as UKS, is an effort made by schools to help students and school residents who are sick in the school area. UKS is usually done in the health room of a school. In another sense, UKS is an effort to foster and develop healthy habits and behavior in school age students which is carried out comprehensively (comprehensively) and integrated (integrative). To optimize the UKS program, the participation of students as subjects and not just objects needs to be increased.